Introduction: A return to politics. (March 2019) - Postero, Nancy; Elinoff, Eli
What does politics mean in contemporary anthropology? Counter to propositions that argue that neoliberalism has produced a "post-political" condition, we argue the notion of a post-political world was never empirically accurate. Instead, using the ethnographic method, our contributors show ongoing and diverse forms of political practices and contestations in the contemporary moment. We reconsider politics at a conceptual level, defining politics as practices of world-making that proceed through the formulation of constellations of critique, disagreement, difference, and conflict. We build this definition through a discussion of contemporary theories of the post-political and agonistic politics, and by tracing a history of political anthropology. Finally, we consider politics as both a practice and a goal. The authors in this collection show that new political anthropologies are particularly attuned to questions of commoning/uncommoning, spaces of articulation and disarticulation, and struggles to live "otherwise." We argue that a return to these questions with a robust and specific engagement with politics is necessary for anthropology and increasingly urgent given the global conjuncture.